(untitled) (Journal of Paediatric Surgeons of Bangladesh, 2016)
Background: Infantile hemangiomas are the most common soft tissue tumors in infancy, Systemic pharmacologic intervention is necessary for endangering, ulcerating, problematic, or life-threatening IHs . These include oral corticosteroid therapy as first-line treatment and interferon - alfa or vincristine as second- or third-line therapeutic agents. Since 2008, use of propranolol has come to the forefront because of its efficacy & minimal side effects. Aims and Objectives: The purpose of this study was to compare the efficacy of orally administered propranolol versus prednisolone versus both in the treatment of potentially disfiguring or functionally threatening infantile hemangiomas. Material and Methods: A prospective study of 24 patients aged 1 week to 12 years child with infantile hemangiomas was randomized into three equal groups. These were as follows: A, Propranolol (12 mg/kg/d); B, Prednisolone (12 mg/kg/d); and C, receiving both for a minimum duration of 3 months. Dimensions, color, consistency, ultrasonography, photographic documentation based on Visual Analogue Scale (VAS) were recorded before and periodically after starting treatment. A minimum 75% improvement was considered as success with no regrowth up to 1 month of stopping treatment. Results: Mean initial response time (days) in A (4.0 ± 3.3 SD) and C (4.5 ± 3.4SD) was significantly lower than B (8.79 ± 7.8SD) Significant change in consistency was noted very early in A (24 hours) compared to B (8days) and C (6 days). VAS results are as follows: (a) color fadingsignificant reduction in A within 48 hours compared to B and C (b) flattening more significant and earlier in A and C than B ,and (c) mean reduction in size: significant in A and C at 3 months), 6 months whereas in B, it was seen only at 6 months. Conclusions: Though its a ongoing study, only result of 24 patient had been analysed. Propranolol had a consistent, rapid therapeutic effect compared to prednisolone. A combination of the two had a comparable but not higher efficacy than propranolol alone. Prednisolone was associated with a higher number of complications, thereby decreasing patient compliance. J. Paediatr. Surg. Bangladesh 5(2): 41-44, 2014 (July)